Decomposition of benzene using char aerosol particles dispersed in a high-temperature filter. (1st January 2017) - Morgalla, Mario; Lin, Leteng; Strand, Michael
Abstract: In this study the tar-removal suitability of char particles finely dispersed in a high-temperature filter was investigated. Benzene was selected as the model tar. An aerosol-based method was designed and used to investigate the benzene decomposition behaviour. Two types of char were used: commercially available activated charcoal and pine char prepared in the laboratory. The conversion behaviour of both chars was investigated in the temperature range between 750 and 900 °C using steam as the gasification medium. During the experiments, different benzene concentrations, amounts of deposited char and gas residence times were tested. The results indicate that both activated carbon and pine char reduced the benzene concentration. Activated carbon generally produced higher and more stable benzene conversions compared to the pine char particles. Decreasing the benzene concentration or increasing the gas residence time or char mass improved the benzene conversion. It was concluded that the char gasification rate became slower while benzene was simultaneously converted. The aerosol-based method was also used to investigate benzene decomposition behaviour while continuously supplying fresh char particles together with steam at 1000 °C. In that way, the deactivated and gasified char particles were steadily replaced, preventing the benzene conversion from decreasing over time. Highlights: Benzene decomposition was examined at 750–1000 °C over finely dispersed chars. The effects of benzene concentration, residence time, and char mass were evaluated. Benzene decomposition was assessed during steady-state char gasification.